A Game of Covid: Strategic Thoughts About a Ludified Pandemic - Raab, Marius Hans; Döbler, Niklas Alexander; Carbon, Claus-Christian (Frontiers in Psychology, 2021)
Many aspects of handling the COVID-19 pandemic bear a resemblance to patterns found in games. We observe point displays and leader boards, the visible assumption of roles, classic archetypes, the collection of resources, and spatial awareness. We argue that these patterns manifest spontaneously as a form of analogical reasoning, because people lack cultural and individual norms as well as cognitive scripts for a pandemic. Trying to find systematic similarities between a novel and a familiar situation is an essential cognitive strategy and a cultural tool, resulting in a spontaneous ludification of this crisis. Unfortunately, most institutions, the media and policymakers focus on attributes that are easy to communicate, not on relations and causal chains. This results in shallow analogies, where the mechanisms and dynamics of COVID-19 are not addressed. This can cause a sense of helplessness, where many people remain passive viewers. A pandemic, however, calls for cooperative action of people who understand the relations between different factors and stakeholders in order to mitigate several negative effects linked to such a crisis. We propose a psychologically founded “Strategic gamification” (here in the context of a pandemic), a form of sense-making that builds on spontaneously emerging ludic elements. By extending upon those elements through the lens of game design, we can shape the mechanics, dynamics and aesthetics of a serious context in a more meaningful way. The resulting analogies have better predictive power and are suited to utilize positive aspects of gamification like engagement, elaboration and collaboration.